Efeitos da terapia com luz azul sobre o ritmo circadiano de atividade-repouso e sobre a expressão de BMAL1 e NeuN do núcleo supraquiasmático de ratos idosos - Silva, Eryck Holmes Alves da (2023)
The effects of aging on circadian rhythms have implications ranging from complex cognitive performance to simple physiological functions. These changes include alterations in the pattern of rhythmic expression, such as a wide fragmentation of the rest-activity rhythm, decrease in amplitude and difficulty in resynchronization regulated by the suprachiasmatic nucleus (SCN). The study of the biological effects of light has received a great current interest, due, among other aspects, to its positive response in psychiatric disorders in humans, such as seasonal depression. However, data with methodological standards on the effects of light are still conflicting and scarce. With that in mind, light therapy can be used to stimulate the SCN to improve its stability in an ontogenetic phase in which various circadian dysregulations occur, possibly due to damage to this pacemaker. The objective of this work is to evaluate the effect of therapy with blue light on the functional aspects of the SCN of aged rats, through the evaluation of the rest-activity rhythm, as well as on possible neuronal changes, with evaluation of NeuN-IR, and neurochemistry, through BMAL1-IR. For this, 43 male Wistar rats (650-690g) aged sixteen months were used. The animals underwent continuous recording of locomotor activity and were exposed for 6 hours to low-intensity blue light (150 lux; peak at 470-490 nm) during the first half of the light phase of the 12:12 h light-dark cycle for 14 days. Some animals were perfused at this stage in ZT6 or ZT12. At the end of blue light therapy, the remaining animals returned to baseline photic conditions for another 14 days, being perfused at the end. After exposure to low-intensity blue light, the animals showed changes in SCN locomotor and neurochemical rhythmicity patterns. It was observed that blue light seems to have a positive effect, promoting an increase in rhythmic robustness, favoring greater consolidation in the resting phase, increasing the circadian function index, in addition to increasing the number of BMAL1-positive cells in the SCN. We believe that our study will serve as a basis for understanding the neurobiological mechanisms of using blue photic exposure as an effective method to minimize circadian disorders of the aged timing system.